Desain Hypothetical Learning Trajectory Sebagai Alternatif Learning Obstacle Pada Materi PLSV - Syabina, Raisya Hizkiya; Ratnaningsih, Nani; Prabawati, Mega Nur (Papanda, 2025)
This study aims to design a Hypothetical Learning Trajectory (HLT) as an alternative approach to overcoming learning obstacles in teaching the topic of linear equations in one variable at the junior high school level. Based on observations and diagnostic tests conducted with 23 seventh-grade students at Junior High School 1 Sariwangi, four major learning obstacles were identified: (1) difficulty in understanding variables as representations of numbers (ontogenic obstacle), (2) difficulty in translating word problems into linear equations of one variable form (ontogenic obstacle), (3) lack of visual aids to grasp the concept of balance (didactical obstacle), and (4) a procedural teaching approach that lacks conceptual reinforcement (didactical obstacle). This research follows the preliminary design phase of a design research methodology, with data collected through observations, diagnostic tests, and qualitative analysis. The findings were used to develop an HLT that includes learning objectives, student activities, predictions of students’ thought processes, and teacher interventions. The HLT was constructed progressively, beginning with real-world contexts, followed by visual representations (model of), conceptual thinking tools (model for), and culminating in symbolic (abstract) solutions. This HLT design is expected to serve as a practical guide for teachers in developing more meaningful, adaptive instruction that aligns with students’ ways of thinking and bridges conceptual difficulties in learning linear equations of one variable.